2012
DOI: 10.4103/1995-705x.99224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and mortality of ST-Segment elevation myocardial- infarction patients receiving thrombolytic -Therapy in the Middle East

Abstract: Objective:Little is known about thrombolytic therapy patterns in patients with ST-elevation myocardial infarction (STEMI) in the Middle East. The objective of this study was to evaluate the clinical profile and mortality of STEMI patients who arrived in hospital within 12 hours from pain onset and received thrombolytic therapy.Patients and Methods:This was a prospective, multinational, multi-centre, observational survey of consecutive acute coronary syndrome patients admitted to 65 hospitals in six Middle East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
(34 reference statements)
1
15
1
Order By: Relevance
“…[4][5][6] In a study comparing the efficacy of thrombolytics in AMI patients, revealed the significantly lower mortality in the patients thrombolysed by reteplase as comparing to streptokinase at 1-year post-AMI follow-up. [7] Above finding is consistent with the present study, in which a significantly lower mortality rate (χ 2 = 3.96, d.f. = 1, P = 0.0466) was observed in the patients of reteplase as compared to streptokinase at 1-year post-AMI follow-up.…”
Section: Discussionsupporting
confidence: 94%
“…[4][5][6] In a study comparing the efficacy of thrombolytics in AMI patients, revealed the significantly lower mortality in the patients thrombolysed by reteplase as comparing to streptokinase at 1-year post-AMI follow-up. [7] Above finding is consistent with the present study, in which a significantly lower mortality rate (χ 2 = 3.96, d.f. = 1, P = 0.0466) was observed in the patients of reteplase as compared to streptokinase at 1-year post-AMI follow-up.…”
Section: Discussionsupporting
confidence: 94%
“…This result was much better than the results reported in previous studies [46, 8, 10, 11, 13–15]. Although the DNT reduction was highly significant, there was no significant reduction in hospitalization days or mortality among either of the groups which is similar to what was found in some previous studies [4, 8, 14], while the analysis by the myocardial infarction triage and intervention trial showed a 7-fold reduction of 30 day mortality in patients treated within 70 minutes [22].…”
Section: Discussioncontrasting
confidence: 73%
“…Tenecteplase (TNK-tPA) is the easiest fibrinolytic to use (it can be given as a single bolus), and in ASSENT-2 trial it was associated with a significantly lower rate of non-cerebral bleeding complications and the need for transfusions compared to reteplase. However, there was no much difference in the rate of intracerebral haemorrhage when compared to alteplase or reteplase 12 13. Tenecteplase is the fibrinolytic agent of choice in many hospitals 14…”
Section: Discussionmentioning
confidence: 99%